Site pre-cast yard layout arrangement through genetic algorithms - Cheung, Sai-On; Tong, Thomas Kin-Lun; Tam, Chi-Ming (Automation in construction, 2002)
The use of modular construction has gained wide acceptance in the housing sector. Standardized modular units are often pre-cast on site. The establishment of site pre-cast yard, in particular arranging the pre-cast facilities within the compound, presents real challenge to site management. This complex task is further aggregated with the involvement of several resources with different transport cost. A GA-model is developed for the search for a near optimal layout solution. The fitness function is to minimize the total transport cost for a pre-determined daily output. The use of the model is illustrated by an example. When compared with the best solution within the initial population, 18.45% reduction in cost for resources flow was achieved by the near optimal layout arrangement arrived at the 673rd trial. It is also suggested that the model can be extended to other layout problems such as warehouse and production line.